2018
DOI: 10.3390/w10111680
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Evaluating the Damage Level of Tooth-Shape Spur Dikes

Abstract: Little research has been done on the application of machine learning approaches to evaluating the damage level of river training structures on the Yangtze River. In this paper, two machine learning approaches to evaluating the damage level of spur dikes with tooth-shaped structures are proposed: a supervised support vector machine (SVM) model and an unsupervised model combining a Kohonen neural network with an SVM model (KNN-SVM). It was found that the supervised SVM model predicted the damage level of the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, machine learning approaches have been widely used for regression [7][8][9][10] and classification [11,12] in water engineering, such as scour depth prediction [13], riprap stone size prediction [14], and rivers dispersion coefficient prediction [15]; these approaches were also applied to predict the settlement of the soft foundation, and a list of these approaches is shown in Table 1. The support vector machine (SVM) was applied to predict the settlement of shallow foundations on cohesionless soils by Samui [16], and the simulation results showed that the SVM could be a practical tool for predicting the settlement of the foundation [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, machine learning approaches have been widely used for regression [7][8][9][10] and classification [11,12] in water engineering, such as scour depth prediction [13], riprap stone size prediction [14], and rivers dispersion coefficient prediction [15]; these approaches were also applied to predict the settlement of the soft foundation, and a list of these approaches is shown in Table 1. The support vector machine (SVM) was applied to predict the settlement of shallow foundations on cohesionless soils by Samui [16], and the simulation results showed that the SVM could be a practical tool for predicting the settlement of the foundation [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Thompson [10] and Hanzawa [6], a damage parameter was proposed to describe the damage condition of the breakwater section, which was a function of the stone density, stone size, wave height, wave number and erosion area in a cross section, while in the studies of van der Meer [2,3] and Kajima [5], a simple damage level was proposed. A summary of the definitions is listed in Table 1 [11]. Table 1.…”
Section: Introductionmentioning
confidence: 99%